Persuasive techniques in Okonjo-Iweala's speech: a study of quasilogical, presentational, and analogical strategies - Kui, Lin Tang,; Sharon Sharmini,; Yasir Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Persuasion is an important aspect of giving a speech. It can be achieved through various persuasive strategies. Past studies related to persuasion have predominantly focused on male politicians’ inauguration, presidential campaigns, and legislative debates, however, not many have focused on speeches delivered by reputable female leaders. Thus, the present study aims to examine the persuasive strategies employed by Okonjo-Iweala in her 2021 International Women’s Day speech. This speech was analysed using Johnstone's (1989) persuasive strategies and the findings showed that she utilised quasilogical (60.86%), presentational (34.79%) and analogical (4.35%) strategies of persuasion in her speech. In other words, quasilogical strategies were used most frequently compared to the other strategies and were expressed through enthymemes, syllogisms, and subordinate clauses (result, conditional, and causal clauses) to relate premises to conclusions in her speech. It was then followed by presentational strategies when Okonjo-Iweala involved her audience and aroused their emotions through the use of rhetorical deixis, repetition, and parallelism in her speech. She also reminded her audience of the importance of gender equality in trade, economics, and leadership with the use of an analogical strategy. This study hopes to contribute to the field of women’s discourse in social practices and persuasive discourse in leadership.